2015
DOI: 10.1080/11263504.2014.998312
|View full text |Cite
|
Sign up to set email alerts
|

Under the shadow of a big plane tree: WhyPlatanus orientalisshould be considered an archaeophyte in Italy

Abstract: In Italy, Platanus orientalis L. is judged as an endangered species by some authors and non-native by others: these contrasting assessments can mislead the prioritization of management actions to preserve the species and the riparian vegetation that is its host. Based on a multidisciplinary approach, including palaeobotanical and ecological information, we assessed its status in Italy including the ecological and conservation value of the riparian plant communities hosting it in the Cilento National Park (S-It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 55 publications
0
11
0
1
Order By: Relevance
“…The occurrence of P. orientalis in proximity of Greek/Roman archaeological sites, the disappearance of Platanus pollen from the Holocene records and its reappearing since the Roman era raises the question whether P. orientalis populations from Southern Italy and Sicily have to be considered remnant of ancient introductions (Rosati et al 2015). However, with the notable exception of a part of the Alento population, which has clear signature of clonal propagation from local genetic resources, current levels of genetic diversity and effective population sizes of Southern Italian and Sicilian populations do not appear to be the result of human-mediated introduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of P. orientalis in proximity of Greek/Roman archaeological sites, the disappearance of Platanus pollen from the Holocene records and its reappearing since the Roman era raises the question whether P. orientalis populations from Southern Italy and Sicily have to be considered remnant of ancient introductions (Rosati et al 2015). However, with the notable exception of a part of the Alento population, which has clear signature of clonal propagation from local genetic resources, current levels of genetic diversity and effective population sizes of Southern Italian and Sicilian populations do not appear to be the result of human-mediated introduction.…”
Section: Discussionmentioning
confidence: 99%
“…Platanus orientalis is, among long-lived tree species, one with the largest leaves in the Mediterranean. Consequently, it has been spread by humans across the Mediterranean for ornamental purposes (mostly for shadow provided for its large canopy) during Greek and Roman times (Rosati et al 2015) and Renaissance (Ciaffi et al 2018). Thus, the actual distribution of this tree may be also explained by the strong human contribution to its dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, soil chemistry change and physical transformation are induced by ploughing, hydrography changes and land reclamation Bosi et al 2014a); the use of fire changes the biomass equilibrium (Bal et al 2011;Sadori et al 2014c); breeding or pastoral activities induce a selection of species towards development of shrubby associations or loss of vegetation (Florenzano & Mercuri 2012) especially under increasing drought (Garcea et al 2013). Consequently, there is the spreading of complex agricultural management (Marvelli et al 2013;Peñ a-Chocarro et al 2013;Masi et al 2014) that archaeobotany has revealed to have been highly advanced in Bronze age (Mercuri et al 2014a and Roman times (Bowes et al 2014); voluntary dispersion of new plants imported for food or decoration (Sadori et al 2009;Rosati et al 2014), and socio-political decisions affecting landscape management (Mensing et al 2013).…”
Section: Collaboration Provides New Insightsmentioning
confidence: 98%
“…In addition to recognition of 'lost species' through plant microfossil identification, syntheses of palaeobotanical, historical, ecological and molecular evidence have also been increasingly used to resolve the conservation status of species with cryptic origins 6,[33][34][35] for example Krauss' clubmoss (Selaginella kraussiana) in the Azores 33 and eastern bluebirds (Sialia sialis bermudensis) on Bermuda 6 . However, many oceanic islands now have high numbers and proportions of species that are considered to be non-natives, in many cases outnumbering native species.…”
Section: Invasive and Non-native Speciesmentioning
confidence: 99%